The Challenges of Machine Translation from Telugu Literary Text to English: Textual and Contextual Analysis - Kolakaluri Madhu Jyoti (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Translation from one language to another is both an art and science. Machine Translation (MT) has been in existence since 1940s and has flourished in recent times due to the proliferation of the web. MT plays predominant role by enabling faster access in getting required translation. However, it is difficult to accept the reality that translation is effective when it comes to literature. Literature is not just a text; it is a collection of expressions, emotions and feelings. Although artificial intelligence is a lead for MT and referred as an intrinsic human quality, it is seldom capable of defining or analysing. Consequently, machine translation particularly for literature facess several challenges. The current paper aims to explore the challenges of MT as an aid used to translate Telugu modern short fiction (Source Language) into English language (Target Language) by online Google Translator (GT). Similarly, the study focusses on various types of language efficacies and textual related hitches such as: semantics, syntax, cohesion and coherence followed by semantics extractions and discourse resolutions. This analysis delves critically into the specific hurdles faced by MT in the context of parsing difference between standard text and machine generated translation.